Digit ratio (2D:4D) and coronary artery disease in north Chinese women. (January 2018) - Wang, Lu; Huo, Zhenghao; Lu, Hong; Bai, Chunyue; Li, Keke; Ma, Wenqian
Abstract: Background: Digit ratio (2D:4D) is fixed in utero and affected by fetal sex steroids. It has been proposed as a putative biomarker of certain hormone- related adult life traits and diseases. Several evidence suggest that 2D:4D ratio may correlate with cardiovascular disease risk (e.g., coronary artery disease). Aims: To investigate whether there is a possible relationship between digit ratio (especially 2D:4D ratio) and coronary artery disease (CAD), and age at CAD in north Chinese women. Methods: Photographs of the two hands of 303 females (controls: 194; patients: 109) were collected. Left hand, right hand and right minus left hand (Dr-l) digit ratio were analyzed and compared. Results: The mean values of digit ratio in patients with CAD were lower than controls for each hand. Significant differences of 2D:4D (left and right hand: P  < 0.01), 2D:5D (left hand: P  < 0.01; right hand: P  < 0.05) and 3D:4D (left hand: P  < 0.01) were found between two groups. There were no associations between 2D:4D ratio and age at CAD on both hands. Conclusion: Decreased digit ratio (especially 2D:4D ratio) may suggest a higher prenatal testosterone (lower prenatal oestrogen) exposure in north Chinese women with coronary artery disease. Highlights: CAD group had significantly lower 2D:4D, 2D:5D in both hands and 3D:4D in left hand than controls. There is no association between 2D:4D and age at CAD. There were no associations between 2D:4D ratio and age at CAD on both hands.